Assessing the Level of Hygienic Practices among Street Food Vendors in Sunyani Township - Sarkodie, Noble Amoako; Bempong, Emmanuel Kofi; Tetteh, Olivia Naa; Saaka, Asana Constance; Moses, Golly Kwaku (Pakistan Journal of Nutrition, 2014)
In recent time, there has been an increased in the springing up of street food vendors across the country and there is therefore an urgent need to ensure that street food vendors adhere to hygienic practices to protect public health. The main aim of the study is to assess the level of hygienic practices of street Food vendors in Sunyani Township. The study adopted descriptive approach and survey was used to gather primary data from 140 respondents. Questionnaires were used to gather data from the respondents and with the help of research assistance the questionnaire were delivered to the premises of the vendors. Data obtained from the study were analyzed by using SPSS and the results were presented in the form of tables. The study revealed that street food vending trade is predominantly a job for women in Sunyani and 85% of the respondents had no any form of training workshop on personal, food and kitchen hygiene. Furthermore, the study revealed that, respondents practiced minimal hygienic practices. The researchers strongly recommended that, Sunyani Metropolitan Assembly should occasionally organized seminars on basic training in personal, kitchen and food hygiene. This is to ensure that they follow the required rules for proper hygiene and sanitation.